An appraisal of social and economic factors that influence the demand for hatchery-bred milkfish fry in Western Visayas. - Francisco, Mariel Latorre
This paper aims to appraise the social and economic factors that influence the demand for hatchery-bred fry in Western Visayas. The study concludes that quality of hatchery-bred fry is the principal consideration of grow-out milkfish operators in deciding whether or not to adopt the new technology. In considering the factors that were ascertained to have influenced the demand for hatchery-bred fry, biological scientists are informed about where they should focus their efforts to redesign the technology in oder to make it more acceptable to fish farmers.